2021
DOI: 10.1371/journal.ppat.1009430
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum malaria drives epigenetic reprogramming of human monocytes toward a regulatory phenotype

Abstract: In malaria-naïve children and adults, Plasmodium falciparum-infected red blood cells (Pf-iRBCs) trigger fever and other symptoms of systemic inflammation. However, in endemic areas where individuals experience repeated Pf infections over many years, the risk of Pf-iRBC-triggered inflammatory symptoms decreases with cumulative Pf exposure. The molecular mechanisms underlying these clinical observations remain unclear. Age-stratified analyses of uninfected, asymptomatic Malian individuals before the malaria seas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 49 publications
3
54
1
Order By: Relevance
“…Since our in vitro system used PBMCs from malaria-naive individuals, it modeled the first infection with malaria, similar to the child patients with malaria in this study. These findings correlate well with another study of patients with malaria in Mali, where the authors found that monocytes from children with no or limited malaria infection history had a more inflammatory response to malaria in in vitro stimulation, whereas monocytes from adults with a history of recurrent malaria infections over their lifespan exhibited a tolerant response ( 34 ).…”
Section: Discussionsupporting
confidence: 89%
“…Since our in vitro system used PBMCs from malaria-naive individuals, it modeled the first infection with malaria, similar to the child patients with malaria in this study. These findings correlate well with another study of patients with malaria in Mali, where the authors found that monocytes from children with no or limited malaria infection history had a more inflammatory response to malaria in in vitro stimulation, whereas monocytes from adults with a history of recurrent malaria infections over their lifespan exhibited a tolerant response ( 34 ).…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, although recent parasitemia was not associated with COVID-19 serostatus or reported symptoms, it is possible that lifetime cumulative malaria exposure could affect COVID-19 severity rather than the recent exposures assessed in this study. While P. falciparum infection of malaria-naïve adults and children may result in a short-lived response ( 23 , 24 ), a sustained skewing of monocytes towards a regulatory phenotype appears to require multiple exposures over the course of several years ( 4 ). As a result, malaria-induced trained immunity or cross tolerance sufficient to affect COVID-19 may require incremental and cumulative malaria exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This may induce tolerance in the host in the long term, and the host becomes tolerant not only to parasite antigens but also to unrelated antigens. Recently, two groups [Guha et al., human field data ( 63 ), and Nahrendorf et al., mouse model data ( 64 )] have shown that monocytes from malaria-exposed individuals differentiate into anti-inflammatory M2-type macrophages. Although their views differed on the locations where monocytes changed to the M2 phenotype, both groups agreed that these changes occurred through epigenetic modifications (a decrease in H3K4me3) at the inflammatory cytokine gene loci.…”
Section: Discussionmentioning
confidence: 99%